Evaluation Of The Stability Of Activator+High-Pull Headgear Therapy - Tamer Türk; Müfide Dinçer (Galenos Yayinevi, 1999)
Numerous views exist on the timing for functional therapy in Class II malocclusions. Different results concerning the dentofacial changes obtained with functional therapies during the pre-peak and peak periods have been may be reached. Regarding the stability of treatment, therapy carried out during the peak period is mentioned to be more advantageous. In this study, retention and post-retention results of activator+high-pull headgear therapy were evaluated. Thirty-one parameters were evaluated from the materials of 17 patients obtained at the beginning of treatment and at the end of the following periods, i.e. active treatment, retention and post-retention. According to their hand-wrist radiographs the subjects were divided into to groups, Pre-peak and Peak groups. The changes occurring during active treatment did not demonstrate any differences between the groups and these changes remained stable during the retention and post-retention periods. Although, the increases of vertical facial heights and mandibular dimensions were more pronounced in the Pre-peak group during all periods, the parameters Go-Gn, N-ANS, N-Gn of the retention period (p<0.05) and the parameters Ar-Go, N-ANS of the post-retention period (p<0.05) demonstrated significant differences between the groups. Activator+high-pull headgear therapy carried out during Pre-peak and Peak periods did not bring forth any different results concerning the therapeutic outcomes and stability. However, the continuation of retention following early treatment would be useful, especially for the control of vertical facial growth.